2023
DOI: 10.1002/eqe.3810
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of ground motion amplitude scaling using interpretable Gaussian process regression: Application to steel moment frames

Abstract: The process of ground motion selection and scaling is an integral part of hazardand risk-consistent seismic demand analysis of structures. Due to the lack of ground motion records that naturally possess high amplitude and intensity, the research community generally relies on scaling the records to match a target hazard intensity level. The scaling factors used are frequently as high as 10. Due to the criticism received in previous research studies, the extent of amplitude scaling and its process has become a m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 16 publications
(12 citation statements)
references
References 60 publications
0
12
0
Order By: Relevance
“…As defined in Equation ( 24), V i can represent the main effect of X i on Y. Then the first-order sensitivity index is calculated by normalizing the main effect by the total variance as Equation (25). The index S i can be interpreted as the average degree of reduction of the total variance when X i is fixed.…”
Section: Variance-based Global Sensitivity Analysis Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…As defined in Equation ( 24), V i can represent the main effect of X i on Y. Then the first-order sensitivity index is calculated by normalizing the main effect by the total variance as Equation (25). The index S i can be interpreted as the average degree of reduction of the total variance when X i is fixed.…”
Section: Variance-based Global Sensitivity Analysis Methodsmentioning
confidence: 99%
“…still requires further in-depth studies to modify the current GPR setting to cope with different cases. Considering the strong ability that the GP model has demonstrated in the existing literature, 25,43,46 its wide application to various types of structures is promising. Besides, the Python package for building GPR (GPyTorch 59 ) selected in this paper allows for customization, which can be adjusted accordingly for specific training results.…”
Section: Further Improvement In the Surrogate Modelmentioning
confidence: 99%
See 1 more Smart Citation
“…6,7 Different selection procedures have been proposed in the literature either with structural or geotechnical purposes. [8][9][10][11][12][13][14][15][16][17][18] However, depending on the adopted compatibility criteria and on the characteristics of the target motion, the selection of a suitable number of compatible actual accelerograms might result impossible without applying large scale factors which distort the characteristics of the selected motions. 14,19,20 This may lead to unrealistic inputs and hence to unreliable predictions of the seismic performance of structural and geotechnical systems 14,[19][20][21][22][23] ; for the latter case, Biondi et al 21 and Aliberti et al 23 have shown that the influence of the input motion selection criteria on the prediction reliability is relevant regardless the complexity level of the analyses.…”
Section: Introductionmentioning
confidence: 99%
“…Since the target ground motion is usually defined in terms of code‐prescribed elastic response spectra, the geotechnical properties of soil affecting the non‐linear site response should be accounted for in the definition of the interval of vibration periods adopted for checking the compatibility of the selected records 6,7 . Different selection procedures have been proposed in the literature either with structural or geotechnical purposes 8–18 . However, depending on the adopted compatibility criteria and on the characteristics of the target motion, the selection of a suitable number of compatible actual accelerograms might result impossible without applying large scale factors which distort the characteristics of the selected motions 14,19,20 .…”
Section: Introductionmentioning
confidence: 99%